Environmental management of energy from biofuels and biofeedstocks - Speight, James G.; Singh, Kamel (Hoboken, New Jersey : John Wiley & Sons, Inc. ; Salem, Massachusetts : Scrivener Publishing, 2014)
This is the most comprehensive and thorough volume on the environmental aspects of energy from biofuels and biofeedstocks. Biomass is a renewable resource whose utilization has received great attention due to environmental considerations and the increasing demands of energy worldwide. Since the energy crises of the 1970s, many countries have become interested in biomass as a fuel source to expand the development of domestic and renewable energy sources, reduce the environmental impacts of energy production, provide rural prosperity for its poor farmers, and bolster a flat agricultural sector.
5.2 Agricultural and Rural Development5.3 Expanding Markets; 5.4 Creating Employment; 5.5 Subsidies; 5.6 Biofuel Processing; 5.7 Biofuels for Local Use; 5.8 Food Versus Fuel Debate; 5.9 Infrastructure Requirements; 5.10 Transport, Storage and Delivery; 5.11 Government Policies and Regulations; References; 6 The Future of Biofuels; 6.1 Introduction; 6.2 Next Generation Biofuels; 6.3 Integrated Refining Concepts -- The Biorefinery; 6.3.1 The Biorefinery Concept; 6.3.2 Process Options; 6.3.3 Anaerobic Digestion; 6.3.4 Fermentation and Hydrolysis; 6.3.5 Transesterification.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Biomass energy; Biomass energy -- Environmental aspects; Chemical processes; Energy crops; Biomass chemicals; Biomass energy; Waste products as fuel; BUSINESS & ECONOMICS -- Real Estate -- General; Biomass energy; Biomass energy -- Environmental aspects; Chemical processes; Energy crops; Electronic books; Electronic books